2022
DOI: 10.1007/s11625-022-01182-3
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging the potential of wild food for healthy, sustainable, and equitable local food systems: learning from a transformation lab in the Western Cape region

Abstract: Food insecurity and diet-related diseases do not only have detrimental effects to human health, but are also underpinned by food systems that are environmentally unsustainable and culturally disconnected. Ensuring access to a healthy, affordable, and sustainable diet is one of the greatest challenges facing many low- and middle-income countries such as South Africa. These challenges in accessing a diverse diet often persist despite biocultural richness. For example, South Africa is globally recognised for its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 88 publications
0
12
0
Order By: Relevance
“…Food insecurity is an issue that many low-and middle-income nations, including South Africa, face [2]. In this study, more than half of the respondents were food insecure as shown in Figure 2.…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations
“…Food insecurity is an issue that many low-and middle-income nations, including South Africa, face [2]. In this study, more than half of the respondents were food insecure as shown in Figure 2.…”
Section: Discussionmentioning
confidence: 67%
“…The South African food system faces wicked challenges; the country has the highest rates of wealth inequality in the world, and there are growing concerns about poverty [1,2]. It is difficult to transition to a healthier, more sustainable, and equitable food system in these circumstances.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…As with fruits supplied to Distell for liqueur production, these fruits are sustainably sourced by community groups of trained harvesters in local villages (Mabaya et al, 2014). This is in line with growing awareness around ethical harvesting, given consumer concerns about the socioeconomic impact of wild fruit use, especially compensation to local communities, and equitable trade practices (Ghanbari et al, 2022;Pereira et al, 2022). Presently, consumers actively look for certification labels on food products to verify that harvesting is environmentally sustainable (Grunert et al, 2014).…”
Section: Market Access and Growthmentioning
confidence: 96%